The Ovitrap Index Measurement of Aedes sp. in Kertasari Urban Village, Ciamis Sub-District Ciamis District - Nurmalasari, Ary; Yanuar Pradani, Firda; Indah Septiani, Nisa; Widiati, Mei (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2024)
Aedes sp. mosquitoes are insects that can transmit dengue fever to humans. Transmission is caused by mosquito bites and mosquito population density in an area can illustrate the potential for dengue transmission. Ovitrap index measurement can be used as one of the efforts to control and prevent dengue fever. This study aims to determine the presence and density of Aedes sp. mosquitoes by the percentage value of the Ovitrap Index (OI) in the Pasirangin neighborhood. In the study, the descriptive method was used by observing ovitraps and calculating the Ovitrap Index on ovitraps in Pasirangin Neighbourhood, RW 09 Kertasari Village. Ovitrap installation was placed inside and outside the house as many as 20 houses. The results showed that of the 40 ovitraps installed, the number of positive ovitraps was 15. Based on the calculation of the overall OI percentage, the result was 37.5 %. The ovitrap index criteria for the research location has a score of 3 (OI below 40 %), which indicates that the area has a moderate potential for dengue disease vulnerability